ФУНКЦІОНАЛЬНІ ПРІОРИТЕТИ о с в іт и НА ХУДОЖНЬО-ГРАФІЧНИХ ФАКУЛЬТЕТАХ (Педагогіка вищої та середньої школи, 2007)
In the article the possibility and prospects of actualization of functions which have a character of communication in a culture in artistic education is considered.